2015
DOI: 10.1515/johh-2015-0031
|View full text |Cite
|
Sign up to set email alerts
|

Examination of aerial diatom flushing across watersheds in Luxembourg, Oregon and Slovakia for tracing episodic hydrological connectivity

Abstract: Hydrological processes research remains a field that is severely measurement limited. While conventional tracers (geochemicals, isotopes) have brought extremely valuable insights into water source and flowpaths, they nonetheless have limitations that clearly constrain their range of application. Integrating hydrology and ecology in catchment science has been repeatedly advocated as offering potential for interdisciplinary studies that are eventually to provide a holistic view of catchment functioning. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
(43 reference statements)
2
8
0
Order By: Relevance
“…This exploratory work confirmed that terrestrial diatoms could be flushed from their terrestrial habitats to the stream—showing that diatoms can be used as tracers of the onset/cessation of surface hydrological connectivity. That initial work was followed up and confirmed by further research and sampling campaigns in experimental catchments located in Oregon and Slovakia—with contrasted physiographic and climatic conditions …”
Section: A Vision For Terrestrial Diatoms In Catchment Hydrology Researchmentioning
confidence: 78%
“…This exploratory work confirmed that terrestrial diatoms could be flushed from their terrestrial habitats to the stream—showing that diatoms can be used as tracers of the onset/cessation of surface hydrological connectivity. That initial work was followed up and confirmed by further research and sampling campaigns in experimental catchments located in Oregon and Slovakia—with contrasted physiographic and climatic conditions …”
Section: A Vision For Terrestrial Diatoms In Catchment Hydrology Researchmentioning
confidence: 78%
“…While, in the past, the emphasis of upscaling has usually been on understanding random spatial variability, the spatial connectivity of flow processes is now increasingly recognized as a key determinant of land use change effects [Bl€ oschl et al, 1995;Western et al, 1998;Van Dijk et al, 2005;Fraser et al, 2013;Band et al, 2014;Pfister et al, 2015]. Forest roads, for example, may increase floods by creating preferential paths of overland flow [Gucinski et al, 2001;Guzman et al, 2017].…”
Section: Upscaling Spatial Connectivity and Scale Dependencymentioning
confidence: 99%
“…Here we build on recent work by Pfister et al (2009Pfister et al ( , 2015 and Wetzel et al (2013) to examine the use of aerial diatoms (i.e. diatoms nearly exclusively occurring outside water bodies, and in wet, moist or temporarily dry places; Van Dam et al, 1994), as natural tracers to infer connectivity in the HRS system.…”
Section: N Martínez-carreras Et Al: Hydrological Connectivity Infermentioning
confidence: 99%